7-10х — 8-8х + 10х+6 = -82х+3 + 3х+4 + 5х+5 = 12 — 7х5х — 3 + 7х — 4 = 8 — 15 — 11х !

( 7-10х) — ( 8-8х) + ( 10х+6) = -8
(2х+3) + (3х+4) + (5х+5) = 12 — 7х
(5х — 3) + (7х — 4) = 8 — (15 — 11х) 
помогите пожалуйста!!

  • Выражение: 7-10*x-(8-8*x)+10*x+6=-8
    1. 7-10*x-8+8*x+10*x+6+8=0
    2. -1+8*x+6+8=0
    3. 13+8*x=0
    Решаем относительно x: x=-13/8=-13/8~~-1.625.
     
    Выражение: 2*x+3+3*x+4+5*x+5=12-7*x
    1. 5*x+3+4+5*x+5-12+7*x=0
    2. 10*x+12-12+7*x=0
    3. 17*x=0
    Решаем относительно x: x=0/17=0. 
    Выражение: 5*x-3+7*x-4=8-(15-11*x)
    1. 12*x-7-8+15-11*x=0
    2. x=0
    Решаем относительно x: x=0.